2023
DOI: 10.14202/vetworld.2023.526-535
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the selection process on malondialdehyde, catalase, superoxide dismutase levels, and the performance of gilts under tropical environmental conditions

Abstract: Background and Aim: Gilt selection has the propensity to improve reproductive performance and promote longevity. However, the impact of this process on oxidative stress biomarker levels remains to be unraveled under tropical conditions. This study aimed to determine the effect of management processes during gilt selection on serum malondialdehyde (MDA), catalase (CAT), superoxide dismutase (SOD) levels, and the performance of replacement gilts under tropical environmental conditions. Materials and Methods: Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…The environment on the other hand played an important role in regulating internal temperature. A study on the impact of environmental condition on gilt performance reported an optimal temperature below 31°C for enhanced performance under tropical condition ( Okafor & Homwong, 2023 ). Though the decrease in light intensity due to seasonal shifts helped to stabilize environmental temperature, the use of evaporative cooling system maintainedinternal temperature at gestation and lactation barns between 25-28°C for most part of the study, reducing the possibility of heat stress.…”
Section: Discussionmentioning
confidence: 99%
“…The environment on the other hand played an important role in regulating internal temperature. A study on the impact of environmental condition on gilt performance reported an optimal temperature below 31°C for enhanced performance under tropical condition ( Okafor & Homwong, 2023 ). Though the decrease in light intensity due to seasonal shifts helped to stabilize environmental temperature, the use of evaporative cooling system maintainedinternal temperature at gestation and lactation barns between 25-28°C for most part of the study, reducing the possibility of heat stress.…”
Section: Discussionmentioning
confidence: 99%